A single-arm clinical trial of a 48-hour intravenous N-acetylcysteine protocol for treatment of acetaminophen poisoning - Heard, K.; Rumack, B. H.; Green, J. L.; Bucher-Bartelson, B.; Heard, S.; Bronstein, A. C.; Dart, R. C. (Clinical toxicology (Philadelphia, Pa.), 2014)
Abstract Introduction. Acetylcysteine prevents hepatic injury when administered soon after acetaminophen overdose. The most commonly used treatment protocols are a 72-hour oral and a 21-hour intravenous (IV) protocol. Between 1984 and 1994, 409 patients were enrolled in a study to describe the outcomes of patients who were treated using a 48-hour IV protocol. In 1991, an interim analysis reported the first 223 patients. The objective of this manuscript is to report the rates of hepatotoxicity and adverse events occurring during a 48-hour IV acetylcysteine protocol in the entire 409 patient cohort. Methods. This was a multicenter, single-arm, open-label clinical trial enrolling patients who presented with a toxic serum acetaminophen concentration within 24 h of acute acetaminophen ingestion. Patients were treated with 140 mg/kg loading dose followed by 70 mg/kg every 4 h for 12 doses. Serum aminotransferase activities were measured every 8 h during the protocol, and adverse events were recorded. The primary outcome was the percentage of subjects who developed hepatotoxicity defined as a peak serum aminotransferase greater than 1000 IU/L. Results. Four hundred and nine patients were enrolled, and 309 met inclusion for the outcome analysis. The overall percentage of patients developing hepatotoxicity was 18.1%, and 3.4% of patients treated within 10 h developed hepatotoxicity. One acetaminophen-related death occurred in a patient treated at 22 h. Adverse events occurred in 28.9% of enrolled subjects; the most common adverse events were nausea, vomiting, and flushing, and no events were rated as serious by the investigator. Conclusions. Acetaminophen-overdosed patients treated with IV acetylcysteine administered as 140 mg/kg loading dose followed by 70 mg/kg every 4 h for 12 doses had a low rate of hepatotoxicity and few adverse events. This protocol delivers a higher dose of acetylcysteine which may be useful in selected cases involving very large overdoses.